2022
DOI: 10.3389/fendo.2022.892342
|View full text |Cite
|
Sign up to set email alerts
|

Organotypic Rat Testicular Organoids for the Study of Testicular Maturation and Toxicology

Abstract: An in vitro system to study testicular maturation in rats, an important model organism for reproductive toxicity, could serve as a platform for high-throughput drug and toxicity screening in a tissue specific context. In vitro maturation of somatic cells and spermatogonia in organ culture systems has been reported. However, this has been a challenge for organoids derived from dissociated testicular cells. Here, we report generation and maintenance of rat testicular organoids in microwell culture for 28 days. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…In the present study, bovine Leydig, Sertoli and peritubular myoid cells were isolated from testes and cultured separately, mixed at a concentration of 1 × 10 6 cells/mL, cultured for 7 days and then transferred to Matrigel for further 3D organization. This protocol differs from those commonly used in 3D testicular models, where testicular cells are obtained through enzymatic digestion and the remotion of connective tissue [ 6 , 8 , 30 , 32 , 34 , 48 ]. These cell isolation protocols may unintentionally provide other cell types to the testicular cell mix, including endothelial-like or uncharacterized cell types that may interfere with further experiments [ 8 , 30 , 31 , 32 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, bovine Leydig, Sertoli and peritubular myoid cells were isolated from testes and cultured separately, mixed at a concentration of 1 × 10 6 cells/mL, cultured for 7 days and then transferred to Matrigel for further 3D organization. This protocol differs from those commonly used in 3D testicular models, where testicular cells are obtained through enzymatic digestion and the remotion of connective tissue [ 6 , 8 , 30 , 32 , 34 , 48 ]. These cell isolation protocols may unintentionally provide other cell types to the testicular cell mix, including endothelial-like or uncharacterized cell types that may interfere with further experiments [ 8 , 30 , 31 , 32 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of Matrigel during culture increases the area where cells can reorganize and permits the formation of larger TOs. Despite the fact that the comparison of diameters and areas of TOs among studies is difficult due to the lack of measurements reported, previous studies have indicated diameters between 100 and 600 μm and average areas around 2966–4628 μm 2 [ 7 , 33 , 34 , 50 , 59 ]. In our study, TOs presented diameters that ranged between 555.15 μm and 1272.88 μm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent studies showed that somatic cell maturation and spermatogonial potential differentiation of rat testicular organoids were higher when incubated at 34 • C than when incubated at 37 • C [19]. Additional studies using in vitro culture models of spermatogonial stem cells (SSC) have demonstrated that high temperatures (37 • C or 43 • C) significantly inhibited SSC differentiation through P53, ribosomes and carbon metabolism signaling pathways, changing their transcriptome [20].…”
Section: Introductionmentioning
confidence: 99%